Small and medium-sized enterprises in the digital business sector - Tehseen, Shehnaz *; Muneeb, D.; Mahmoud, A. B.; Hack-Polay, D.; Yeong, H. Y.; Nawaz, F. (IGI Global, 2021)
The chapter is a systematic literature review of fundamental theories about small and medium business (SME) success. The chapter examines how they specifically impact digital SMEs. The chapter examined six theories: dynamic capability view (DCV), composition-based view of firm growth (CBV), resourcebased view (RBV), resource dependence theory (RDT), upper echelon theory (UET), strategic contingency theory (SCT). The results showed that RBV, DCV, and UET become relevant in articulating the value inherent to the internal resources in SMEs (which render their capabilities dynamic). In contrast, the SCT framework and the RDT model show more significance in relation to uncertainty and contingency. CBV was found to be a more pertinent framework to predict the success of SMEs. The results support CBV’s hypothesis that SMEs (including digital SMEs) are able to be competitive without extensive resource advantage, too complicated technologies, or market power. The increased deployment of CBV can be advocated as a critical determinant of digital SME success.